A Study on Developing Critical Thinking of College Students through CRD in Comprehensive English Class - Bai, Lei (Pacific International Journal, 2022)
To cultivate independent innovation capability has become the core goal of the Higher Education in China and also an important indicator to display national strength. The critical thinking ability is the premise and foundation of innovative capability. Therefore, there is a pressing need to to develop critical minds of the college students in daily teaching. This research aims to explore the effective ways of developing critical thinking (CT) competence through collaborative reasoning discussions (CRD). It conducts a detailed analysis of how to integrate the objective of developing CT skills in collaborative reasoning discussions (CRD), so as to provide the reference for the practice of critical thinking research and come up with the proper teaching mode for critical thinking in China.